1987
DOI: 10.1159/000234400
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Reactivity of Conjugates of N-Formyl-Methionyl-Leucyl-Phenylalanine and Rye-Grass Pollen Allergens

Abstract: Conjugates of rye-grass pollen extract and N-formyl-methionyl-leucyl-phenylalanine were prepared using an activated form of the tripeptide. Introduction of the peptide into the extract brought about an extensive reduction of reactivity with grass-pollen-specific IgE, as measured by RAST inhibition. Despite this loss, guinea pig alveolar macrophages and murine splenic macrophages readily presented the conjugates to T lymphocytes specific for grass pollen allergens and caused their proliferation in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…This paper has extended the finding previously re ported that modification of rye grass pollen extract with the peptide formyl-methionyl-leucyl-phenylalanine led to a reduction of its reactivity with specific human IgE, without affecting its reactivity with T cells from guinea-pigs and mice [17], Evidence pre sented here has shown that T cells specific for rye grass pollen extract and the two major allergens R7 and R14a were induced in mice following immuniza tion both with unmodified rye grass pollen extract and with a highly substituted F-MLP/rye conjugate. These cells responded both to the grass pollen extract and to the purified allergens in two assay systems, one involving antigen presentation to purified T cells via syngeneic accessory cells and the other a standard lymphocyte transformation assay using unseparated lymph node cells.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This paper has extended the finding previously re ported that modification of rye grass pollen extract with the peptide formyl-methionyl-leucyl-phenylalanine led to a reduction of its reactivity with specific human IgE, without affecting its reactivity with T cells from guinea-pigs and mice [17], Evidence pre sented here has shown that T cells specific for rye grass pollen extract and the two major allergens R7 and R14a were induced in mice following immuniza tion both with unmodified rye grass pollen extract and with a highly substituted F-MLP/rye conjugate. These cells responded both to the grass pollen extract and to the purified allergens in two assay systems, one involving antigen presentation to purified T cells via syngeneic accessory cells and the other a standard lymphocyte transformation assay using unseparated lymph node cells.…”
Section: Discussionsupporting
confidence: 76%
“…The conjugate used in this study was an extensively modified sam p le d escribed in detail in an earlie r p u b lication [ 17], Briefly, rye grass pollen extract (30 mg) was reacted with an activated ester of F-MLP (58 mM). Characterization of the conjugate showed that 78% of the available primary amino groups of the extract had been modified, and that its reactivity with specific IgE was reduced ap proximately 1,000-fold as measured by RAST inhibition [7],…”
Section: F-mlp/rye Grass Pollen Extract Conjugate (F-mlp/rye)mentioning
confidence: 99%
See 1 more Smart Citation
“…Modified RE samples were those described in a number of pre vious publications (table I): polysarcosine-RE [6]; f met-leuphe-RE [7]; chemically (cyanogen bromide and thiocyanonitrobenzoic acid) fragmented RE [8], and enzymatically (chymotrypsin) fragmented RE [9].…”
Section: Modified Allergensmentioning
confidence: 99%
“…Although this form of treatment is generally considered to be beneficial, the local and systemic anaphylactic side effects of the therapy can be serious [2,3]. Considerable effort, therefore, has been expended in a search for allergen forms with re duced allergenicity but maintained efficacy [4], Modified allergens that have mainly T-cell-stimulating properties retained have been proposed as candidates for safer therapy [5], such as conjugates of polysarcosine [6] or f met-leu-phe [7] and grass pollen extract, and both chemically [8] and enzymatically [9] produced cleavage products of allergens. Experimen tal animal systems are often used for evaluation of these potential-therapeutic agents [10] but a more rele vant system using human lymphocytes would be of advantage.…”
Section: Introductionmentioning
confidence: 99%